Controversies in Surgical Staging of Endometrial Cancer. (23rd June 2010) - Seracchioli, R.; Solfrini, S.; Mabrouk, M.; Facchini, C.; Di Donato, N.; Manuzzi, L.; Savelli, L.; Venturoli, S.
Abstract : Endometrial cancer is the most common gynaecological malignancy and its incidence is increasing. In 1998, international federation of gynaecologists and obstetricians (FIGO) required a change from clinical to surgical staging in endometrial cancer, introducing pelvic and paraaortic lymphadenectomy. This staging requirement raised controversies around the importance of determining nodal status and impact of lymphadenectomy on outcomes. There is agreement about the prognostic value of lymphadenectomy, but its extent, therapeutic value, and benefits in terms of survival are still matter of debate, especially in early stages. Accurate preoperative risk stratification can guide to the appropriate type of surgery by selecting patients who benefit of lymphadenectomy. However, available preoperative and intraoperative investigations are not highly accurate methods to detect lymph nodes and a complete surgical staging remains the most precise method to evaluate extrauterine spread of the disease. Laparotomy has always been considered the standard approach for endometrial cancer surgical staging. Traditional and robotic-assisted laparoscopic techniques seem to provide equivalent results in terms of disease-free survival and overall survival compared to laparotomy. These minimally invasive approaches demonstrated additional benefits as shorter hospital stay, less use of pain killers, lower rate of complications and improved quality of life.